Leveling up your personality : a practical guide - Bunyi, Albina Sacramento (Mandaluyong, Philippines : Books Atbp. Publishing Corp., 2022)
This book presents realistic and closely related approaches and techniques in each of the seven components, mostly drawn from the points of view of various authorities in the field of personality development and other related disciplines, and complemented with my three-decade observations and experiences.
Introduction -- Foundations of personality -- Physical attributes of personality -- Personality traits -- Psychological attributes of personality -- Stress -- Motivation -- Emotions and mental health -- The moral and spiritual aspects of personality -- Human relations -- Leadership -- Communication -- Good manners and decorum -- Personality measurement.
Includes bibliographical references.
Keywords: PERSONALITY DEVELOPMENT